Rethinking Balkanism: interpretative challenge of the early modern Illyrism - Blažević, Zrinka (2007)
The first part of the paper is aimed at reconstructing epistemic genealogy of the "Balkanism" as well as to trace its complex and often conflict relationship with the postcolonial theory. Thereafter, on the ground of the three key postcolonial concepts - liminality, hybridity and transculturation – it is argued how interdisciplinary exchange and mutuality between post-colonial theory and Balkan studies could bring about useful heuristic models and research protocols for the examination of the complex cultural scenery of the Balkans. The complex and polyphonic character of the Balkanist discourse is illustrated on the example of the early modern Illyrism, which could be read as a kind of discursive heterotopia. A short overview of the construction process of the early modern Illyrism elucidates how this complex discursive amalgam simultaneously produced transnational Panslavic identity and distinctive and exclusivist South/Slavic identities.
Projekt MZOS
Projekt MZOS
ENG